Real Exchange Rates in Growing Economies : How Strong Is the Role of the Nontradables Sector? - Miyajima, Ken (IMF Working Papers; Working Paper ;, 2005)
This paper emphasizes the importance of total factor productivity (TFP) developments in the nontradables sector to quantitatively demonstrate that the time-honored Balassa-Samuelson hypothesis does not generally apply to episodes of economic growth. Though the Balassa- Samuelson hypothesis postulates that strong economic growth should, in general, be accompanied by a real appreciation in exchange rates, this paper does not find such systematic links. This is because some growth spurts are marked by equal TFP gains in both the tradables and nontradables sectors, and others by larger TFP gains in the nontradables sector.